2016
DOI: 10.1002/2015jd024524
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of lightning, sprites, and human‐induced emissions observed by nadir‐viewing cameras on board the International Space Station

Abstract: The Lightning and Sprites Observation (LSO) experiment was designed to test a new concept of nadir-viewing sprite measurement on board the International Space Station using spectral differentiation methods for lightning and sprite identification. It was composed of two calibrated cameras: one equipped with a narrowband filter at 763 nm to maximize the contrast between sprites and lightning, and the other to monitor lightning. The LSO was operated at night during 15 days from 2001 to 2004 during which 197 light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Averaged across the Congo Basin, Crowhurst et al (2020) found that the best performing global climate models (GCMs) with low root mean square errors against CHIRPS2 rainfall (Funk et al 2015) have slightly higher rainfall at the November rainfall peak than the March rainfall peak. While this agrees with several studies (Haensler et al 2013;Washington et al 2013;Creese and Washington 2016), and several reanalyses ( Fig. 1a, Table 1), the CHIRPS2 data set, which has the best agreement of 10 satellite and gauge -year mean (1989-2005) seasonal cycles of a rainfall (mm day −1 ) and b evaporation (mm day −1 ) averaged over the Congo Basin (14° S-4° N, 18° E-30° E), from four reanalyses, CFSR (Saha et al 2010), ERA5-Land (Hersbach et al 2020), MERRA-2 (Gelaro et al 2017) and NCEP-2 (Kanamitsu et al 2002), and two reference data sets, CHIRPS2 rainfall (Funk et al 2015) and LandFlux-EVAL evaporation (Mueller et al 2013) rainfall products against the NIC131-Gridded rainfall dataset in the Congo Basin (Nicholson et al 2019), has a similar amount of rainfall at the two peaks ( Fig.…”
Section: Lower Evaporation In November Than March In the Congo Basinsupporting
confidence: 93%
“…Averaged across the Congo Basin, Crowhurst et al (2020) found that the best performing global climate models (GCMs) with low root mean square errors against CHIRPS2 rainfall (Funk et al 2015) have slightly higher rainfall at the November rainfall peak than the March rainfall peak. While this agrees with several studies (Haensler et al 2013;Washington et al 2013;Creese and Washington 2016), and several reanalyses ( Fig. 1a, Table 1), the CHIRPS2 data set, which has the best agreement of 10 satellite and gauge -year mean (1989-2005) seasonal cycles of a rainfall (mm day −1 ) and b evaporation (mm day −1 ) averaged over the Congo Basin (14° S-4° N, 18° E-30° E), from four reanalyses, CFSR (Saha et al 2010), ERA5-Land (Hersbach et al 2020), MERRA-2 (Gelaro et al 2017) and NCEP-2 (Kanamitsu et al 2002), and two reference data sets, CHIRPS2 rainfall (Funk et al 2015) and LandFlux-EVAL evaporation (Mueller et al 2013) rainfall products against the NIC131-Gridded rainfall dataset in the Congo Basin (Nicholson et al 2019), has a similar amount of rainfall at the two peaks ( Fig.…”
Section: Lower Evaporation In November Than March In the Congo Basinsupporting
confidence: 93%
“…This raises the possibility of connections between model biases in the Congo region and those in southern Africa. However, the lack of observational data in the Congo makes it very difficult to evaluate these biases [e.g., Washington et al, 2013], and process-based model evaluation is needed to help constrain model rainfall estimates [Creese and Washington, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Another source of images of the Earth at night from the ISS is dedicated instrumentation on the ISS. For example, the experiment LRO (Lightning and Sprites Observation) (Farges et. al.…”
Section: Additional Night-time Sensors On the Issmentioning
confidence: 99%